2013
DOI: 10.1037/a0032323
|View full text |Cite
|
Sign up to set email alerts
|

Toward secure attachment in adolescent relational development: Advancements from sandplay and expressive play-based interventions.

Abstract: This article provides a comprehensive literature review of the most current research in adolescent attachment, as well as clinical implications for play therapists who recognize the significance of the therapeutic dyad when working with adolescents. Additionally, the article discusses case studies involving the integration of expressive art therapy interventions, such as sandplay (Donald, 2003; Green 2012), to strengthen the adolescent's overall schema of attachment to 'secure.'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Positive engagement with parent(s) at baseline was associated with enhanced self-esteem and lower internalizing problems over the subsequent 2-year period. The interpretation is clear: with the security of strong attachment bonds with parents, adolescents are likely to thrive, showing many signs of positive development; however, conflict that disrupts these bonds and attenuates parent support pushes adolescents to be self-critical, despondent, anxious, and engage in risk-taking behavior (Green et al, 2013). Parents are a primary source of all types of social capital (e.g., social, educational, cultural, financial capital) development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive engagement with parent(s) at baseline was associated with enhanced self-esteem and lower internalizing problems over the subsequent 2-year period. The interpretation is clear: with the security of strong attachment bonds with parents, adolescents are likely to thrive, showing many signs of positive development; however, conflict that disrupts these bonds and attenuates parent support pushes adolescents to be self-critical, despondent, anxious, and engage in risk-taking behavior (Green et al, 2013). Parents are a primary source of all types of social capital (e.g., social, educational, cultural, financial capital) development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a longitudinal study of Hispanic and African American middle school students, decreases in guardian support over a 1-year period were associated with increased internalizing symptoms (Rosario et al, 2008). Without the security of strong relationships with parents, adolescents are more likely to become despondent and anxious and engage in risk-taking behavior (Green, Myrick, & Crenshaw, 2013). Given that parents are a primary provider of social capital, conflict in the parent–child relationship blocks this outlet for positive social capital development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reflecting skills in play therapy model attunement and relational security for adoptive family members of any age (Green, Myrick, & Crenshaw, 2013). As an expressive play modality, sandtray therapy strongly accomplishes these therapeutic goals.…”
Section: Sandtray Therapy As Attachment-friendlymentioning
confidence: 97%
“…The relevance of attachment in typical adolescent development from the play therapy paradigm has recently been addressed in the literature (Green, Myrick, & Crenshaw, 2013). Researchers have found that early caregiving relationships provide the context within which adolescents come to understand themselves, others, and themselves in relation to others.…”
Section: Impairment In Attachmentmentioning
confidence: 99%